2018
DOI: 10.1038/s41598-018-29195-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Transport and Power Dissipation in Aerosol-Jet-Printed Graphene Interconnects

Abstract: This paper reports the first known investigation of power dissipation and electrical breakdown in aerosol-jet-printed (AJP) graphene interconnects. The electrical performance of aerosol-jet printed (AJP) graphene was characterized using the Transmission Line Method (TLM). The electrical resistance decreased with increasing printing pass number (n); the lowest sheet resistance measured was 1.5 kΩ/sq. for n = 50. The role of thermal resistance (RTH) in power dissipation was studied using a combination of electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…Electrical breakdown was likely due to the high porosity causing trapped gases and solvents within interconnects, as well as weak interlayer bonding of graphene flakes. Furthermore, power dissipation was dominated by the graphene interconnect morphology for substrates with high thermal conductivity (e.g., Al 2 O 3 substrate); however, power dissipation can be limited by polymer substrates with low thermal conductivity (e.g., polyimide substrate) . Aerosol jet printing has been proved to be a suitable method for printing large‐area, CNT‐based transistors on flexible substrate, which will be summarized in Section .…”
Section: Printing Conductive Nanomaterials Inksmentioning
confidence: 99%
“…Electrical breakdown was likely due to the high porosity causing trapped gases and solvents within interconnects, as well as weak interlayer bonding of graphene flakes. Furthermore, power dissipation was dominated by the graphene interconnect morphology for substrates with high thermal conductivity (e.g., Al 2 O 3 substrate); however, power dissipation can be limited by polymer substrates with low thermal conductivity (e.g., polyimide substrate) . Aerosol jet printing has been proved to be a suitable method for printing large‐area, CNT‐based transistors on flexible substrate, which will be summarized in Section .…”
Section: Printing Conductive Nanomaterials Inksmentioning
confidence: 99%
“…This creates a large contact area which results in a reduced interface resistance and less porous film. However, similar to graphene films, AJP results in an increase in porosity due to the random stacking of nanoplates as they adhere to the polyimide substrate, [ 52 ] as well as potentially trapping solvents within the printed features. The solvents evaporate leaving behind pores, thus resulting in a larger electrical resistivity.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the Seebeck coefficient was −64 µV K −1 . The decrease in electrical conductivity of aerosol jet printed films can be attributed to the increase in porosity, [ 52 ] which also impacts the Seebeck coefficient. Due to the random arrangements of nanoplates and high amount of porosity, this hinders the interaction between the nanoparticles which results in a lower electrical conductivity and poor Seebeck voltage.…”
Section: Resultsmentioning
confidence: 99%
“…In our research, we investigated power dissipation and electrical breakdown in aerosol jet-printed graphene (with N 2 carrier gas) interconnects on Kapton, SiO 2 /Si, and Al 2 O 3 substrates [ 135 ]. Our study indicated that the power dissipation in AJP graphene is dominated by the graphene interconnect morphology for high thermal conductivity substrates but can be limited by the substrate properties.…”
Section: Advanced Printing Techniquesmentioning
confidence: 99%